STUDENTS' LISTENING COMPREHENSION, COMPARATIVE STUDY BETWEEN INTERNATIONAL STANDARD SCHOOL AND THOSE IN REGULAR SCHOOL - Sri Hastuti, - (2011)
Indonesia government founded international standard schools in each district which applies bilingual class. Students of international standard school are expected to be able to improve their English skills. This study was descriptive study which aimed to compare listening comprehension of students of international standard school and regular school in Cirebon. The data were taken from listening comprehension test and class observation which was analyzed using theories adapted from Martinez, at al. (2000) and Brown (2000). The test result using statistical analysis with t-test showed that there was a difference of listening comprehension between students of International Standard School and those of non International Standard School while the observation result found that there were three factors which influenced students' listening comprehension, they were frequency of using English by teacher and types of listening performance found during teaching learning process. This study indicates that regular school needs to improve their teaching English.